Activation of Oxygen evolving Perovskites for Oxygen Reduction by Functionalization with Fe-Nx/C groups - Rincón, Rosalba A.; Masa, Justus; Mehrpour, Sara; Tietz, Frank; Schuhmann, Wolfgang (Chemical communications, 2014)
The incorporation of Fe–Nx/C moieties into perovskites remarkably activates them for the oxygen reduction reaction (ORR) and also leads to notable improvement of their activity towards the oxygen evolution reaction (OER) thus presenting a new route for realizing high performance, low cost bifunctional catalysts for reversible oxygen electrodes.